Tafsir Tematik Tentang Kafa’ah (Kesepadanan) dalam Perkawinan: Analisis Hukum Keluarga Perspektif Al-Quran - Elliani Fikriyah; Ali Khosim; Athoillah Athoillah (JURNAL ILMIAH NUSANTARA, 2026)
The concept of kafa'ah or equivalence in marriage is one of the fundamental principles in Islamic family law that aims to maintain harmony and social balance. The Qur'an does not mention the term kafa'ah explicitly, but the principle of equivalence is emphasized through QS. an-Nūr: 26, QS. an-Nisā': 25, and QS. al-Ḥujurāt: 13, which emphasizes that ideal equivalence in marriage focuses on the balance of faith, morals, and piety, not social or economic status. The understanding of kafa'ah in the contemporary context has undergone a reinterpretation, shifting from a focus on socio-structural status to an emphasis on ethical-religious aspects, relevant within the framework of maqāṣid al-syarī‘ah to realize welfare and justice. This study uses the thematic interpretation method to analyze the concept of kafa'ah in the Qur'an and its implications in contemporary Islamic family law. The research results show that kafa'ah should be understood as the equivalence of religious values, visions, and responsibilities, not simply equality of social or economic status.